New insights for phase‐change immersion cooling enhancement of solar cells under high concentration ratios. (2nd August 2017) - Kang, Xue; Wang, Yiping; Huang, Qunwu; Cui, Yong; Shi, Xusheng; Wang, Chen; Fan, Jiangyang
Summary: To answer how surface corrosion affects the heat transfer performance of phase‐change immersion cooling solar cells, electrochemical etching was used for substrate surface treatment of simulated dense‐array solar cells in this paper. Morphology, roughness, and wettability of treated surfaces were characterized by scanning electron microscope, atomic force microscope, and spreading area, respectively. A self‐running cooling system was developed to investigate the effect of surface treatment on self‐running characteristics and heat transfer performance under different ethanol inlet temperatures and concentration ratios. The results show that the surface treated for 2 hours owns higher wettability because of the honeycomb‐like porous structure. Lower ethanol flowing velocity obtained under lower ethanol inlet temperature with treated samples. The maximum declined degree in the wall superheating of 21.1% and the maximum enhancement in the heat transfer coefficient of 33.3% are obtained for sample treated for 2 hours because of its higher wettability and porosity structure. The results show that electrochemical etching on substrate surface can improve the phase‐change immersion cooling performance of solar cells. Abstract : GA: Heat transfer enhancement mechanism of surface modification.